A Comparative Study Between Effects of Some Antioxidants on Levels of Hormones in Male Rabbits - Eman Saad; Mariam Ibrahim; Fayrouz Khaled; Marfoua Ali (AlQalam Journal of Medical and Applied Sciences, 2020)
Backgrounds: A. Muricata is a genus of tropical fruit trees belonging to the family Annonaceae, that contains chemical compounds exhibiting antitumor, pesticidal, antiviral and antimicrobial effects, thus signifying several potentially beneficial applications. Ginger such as zingerone, gingerdiol, zingibrene, gingerol and shogaols have shown antioxidant activities. Panax ginseng is one of the most widely used medicinal plants for the treatment of various diseases. This study was aimed to compare the effects of these antioxidants on levels of some hormones in male rabbits. Methods: Animals were assigned to one of four treatment groups: control group, 100 mg A. muricata, 100 mg ginger or 100 mg ginseng/kg BW. Testosterone, estradiol and progesterone hormone concentrations were assayed by using commercial kit. Results: Overall, the three plants show similar effect on different measured parameters. Results obtained showed that treatment with A. muricata, ginger or ginseng caused significant (P<0.05) increase body weight, relative testes weight, testosterone, progesterone, estradiol, T3 and T4 in serum of blood compared to control. A. muricata and ginseng were more effective than ginger. Conclusion. Treatment of rabbit with A. muricata, ginger or ginseng has ameliorative effects on the fertility, hormonal status and may have curiously applications in regenerative.